Respuesta :
Answer:
[tex]x = \frac{17}{18}[/tex]
[tex]y = \frac{23}{6}[/tex]
Step-by-step explanation:
Given
[tex]y = 3x + 1[/tex]
[tex]Points = (0,0)\ to\ (-3,4)[/tex]
Required
Determine (x,y) equidistant from the equation and the given point
This question will be answered using distance formula;
[tex]d = \sqrt{(x_1 - x_2)^2 + (y_1 - y_2)^2}[/tex]
Considering The first Point [tex](0,0)\ to\ (x,y)[/tex]
[tex](x_1 ,y_1) = (0,0)[/tex]
[tex](x_2,y_2) = (x,y)[/tex]
The distance is:
[tex]d = \sqrt{(x_1 - x_2)^2 + (y_1 - y_2)^2}[/tex]
[tex]d = \sqrt{0 - x)^2 + (0 - y)^2}[/tex]
[tex]d = \sqrt{(- x)^2 + (- y)^2}[/tex]
[tex]d = \sqrt{x^2 + y^2}[/tex]
Considering the second point: [tex](x,y)\ to\ (-3,4)[/tex]
[tex](x_1,y_1) = (x,y)[/tex]
[tex](x_2,y_2) = (-3,4)[/tex]
The distance is:
[tex]d = \sqrt{(x_1 - x_2)^2 + (y_1 - y_2)^2}[/tex]
[tex]d = \sqrt{(x - (-3))^2 + (y - 4)^2}[/tex]
[tex]d = \sqrt{(x + 3)^2 + (y- 4)^2}[/tex]
[tex]d = \sqrt{x^2 + 6x + 9 + y^2- 8y + 16}[/tex]
[tex]d = \sqrt{x^2 + 6x + y^2- 8y + 16 + 9}[/tex]
[tex]d = \sqrt{x^2 + 6x + y^2- 8y + 25}[/tex]
Equate both values of d
[tex]\sqrt{x^2 + 6x + y^2- 8y + 25} = \sqrt{x^2 + y^2}[/tex]
Square both sides
[tex]x^2 + 6x + y^2- 8y + 25 = x^2 + y^2[/tex]
Collect Like Terms
[tex]6x - 8y + 25 = x^2 -x^2+ y^2 -y^2[/tex]
[tex]6x - 8y + 25 =0[/tex]
Recall that [tex]y = 3x + 1[/tex]
[tex]6x - 8(3x + 1) + 25 = 0[/tex]
[tex]6x - 24x - 8 + 25 = 0[/tex]
[tex]-18x+ 17 = 0[/tex]
[tex]-18x=- 17[/tex]
Solve for x
[tex]x = \frac{-17}{-18}[/tex]
[tex]x = \frac{17}{18}[/tex]
Substitute [tex]\frac{17}{18}[/tex] for x in [tex]y = 3x + 1[/tex]
[tex]y = 3 * \frac{17}{18} + 1[/tex]
[tex]y = \frac{17}{6} + 1[/tex]
[tex]y = \frac{17 + 6}{6}[/tex]
[tex]y = \frac{23}{6}[/tex]